Kinematic characteristics of the ski jump inrun: A 10-year longitudinal study - Janura, M.; Cabell, L.; Elfmark, M.; Vaverka, F. (Journal of Applied Biomechanics, 2010)
The athlete`s inrun position affects the outcome for take-off in ski jumping. The purpose of this study was to examine the kinematic parameters between skiers` adjacent body segments during their first straight path of the inrun. Elite ski jumpers participated in the study at the World Cup events in Innsbruck, Austria, during the years 1992 through 2001. A video image was taken at a right angle to the tracks of the K-110 (meter) jumping hill. Kinematic data were collected from the lower extremities and trunk of the athletes. Findings indicated that jumpers had diminished ankle and knee joint angles and increased trunk and hip angles over the 10 years. In recent years, the best athletes achieved a further length of their jumps, while they experienced slower inrun average velocity. These results are perhaps explained by several possible contributing factors, such as new technique of the jumper`s body kinematics, advancements in equipment technology, and somatotype of the jumpers.